Electronic Student Worksheet Based on Problem Solving on Addition and Subtraction Integers Mathematics Grade 4 - Dyah Triwahyuningtyas; Refanda Tri Cahyono; Nyamik Rahayu Sesanti (Jurnal Ilmiah Sekolah Dasar, 2025)
The suboptimal use of technology in learning has contributed to low levels of students’ critical thinking and problem-solving skills, particularly in elementary mathematics instruction. This condition indicates the need for innovative learning media that systematically facilitate higher-order thinking processes. This study aims to develop, analyze the feasibility, practicality, and examine the effectiveness of a problem-solving–based electronic student worksheet (e-LKPD) supported by a website for teaching addition and subtraction of integers to fourth-grade elementary students. The study employed a Research and Development (R&D) approach using the ADDIE model, which consists of the analysis, design, development, implementation, and evaluation stages. The research subjects included elementary school students and teachers as users of the developed product. Data were collected through expert validation involving content, language, and media specialists to assess feasibility, student and teacher response questionnaires to evaluate practicality, and pretests and posttests to measure effectiveness. Data analysis was conducted using descriptive quantitative and inferential techniques, including N-gain analysis. The results indicate that the developed e-LKPD is categorized as highly feasible and highly practical, and it effectively improves students’ learning outcomes as well as their critical thinking skills. These findings suggest that problem-solving based e-LKPD supported by a website can serve as an innovative alternative learning medium that promotes meaningful mathematics learning in elementary education.